2011
DOI: 10.1155/2011/130467
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Household Behavioral Risk Factors for Diarrheal Disease in Dar es Salaam: A Photovoice Community Assessment

Abstract: Whereas Tanzania has seen considerable improvements in water and sanitation infrastructure over the past 20 years, the country still faces high rates of childhood morbidity from diarrheal diseases. This study utilized a qualitative, cross-sectional, modified Photovoice method to capture daily activities of Dar es Salaam mothers. A total of 127 photographs from 13 households were examined, and 13 interviews were conducted with household mothers. The photographs and interviews revealed insufficient hand washing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…Articles have been grouped according to: (1) water governance themes and concerns addressed, identified under the category ‘specific objective of the study,’ and (2) geographical focus, identified under the categories ‘participants (place)’ and ‘urban/rural.’ The four groups thus identified are:Projects identifying issues and concerns in water and health, sanitation, hygiene (six articles27, 28, 29, 30, 31, 32 and five projects): these studies have been undertaken in Sub‐Saharan Africa (South Africa, Mozambique, Kenya, and Tanzania) by researchers based in Canada and the United States with local African partners.Projects promoting participation in water resources management (eight articles19, 33, 34, 35, 36, 37, 38, 39 and eight projects), in Australia and New Zeeland undertaken by national research groups, and in India by an international consortium of Australian and Indian researchers.Projects aiming at understanding experiences and perceptions of landscapes and water spaces (five articles40, 41, 42, 43, 44 and four projects): these projects have been undertaken in Canada (2) and Japan (1) by national research groups and in Sierra Leone (1) by a researcher based in Canada.Projects aiming to explore the link between domestic water and urban water management (four articles20, 45, 46, 47 and three projects) undertaken in Australia (2) and New Zeeland (1) by national research groups. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Articles have been grouped according to: (1) water governance themes and concerns addressed, identified under the category ‘specific objective of the study,’ and (2) geographical focus, identified under the categories ‘participants (place)’ and ‘urban/rural.’ The four groups thus identified are:Projects identifying issues and concerns in water and health, sanitation, hygiene (six articles27, 28, 29, 30, 31, 32 and five projects): these studies have been undertaken in Sub‐Saharan Africa (South Africa, Mozambique, Kenya, and Tanzania) by researchers based in Canada and the United States with local African partners.Projects promoting participation in water resources management (eight articles19, 33, 34, 35, 36, 37, 38, 39 and eight projects), in Australia and New Zeeland undertaken by national research groups, and in India by an international consortium of Australian and Indian researchers.Projects aiming at understanding experiences and perceptions of landscapes and water spaces (five articles40, 41, 42, 43, 44 and four projects): these projects have been undertaken in Canada (2) and Japan (1) by national research groups and in Sierra Leone (1) by a researcher based in Canada.Projects aiming to explore the link between domestic water and urban water management (four articles20, 45, 46, 47 and three projects) undertaken in Australia (2) and New Zeeland (1) by national research groups. …”
Section: Resultsmentioning
confidence: 99%
“…Projects identifying issues and concerns in water and health, sanitation, hygiene (six articles27, 28, 29, 30, 31, 32 and five projects): these studies have been undertaken in Sub‐Saharan Africa (South Africa, Mozambique, Kenya, and Tanzania) by researchers based in Canada and the United States with local African partners.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 of my respondents in 2014 spent at least 5 minutes queuing at their primary water sources, with some spending over 30 min. Badowski et al (2011) found waiting time could be up to 30 min. Acknowledging the burden that walking and waiting can have on households, the Tanzanian Government has a long-term goal of a 5-min roundtrip water collection time (MoWLD, 2002).…”
Section: Water Collection Burdenmentioning
confidence: 99%
“…Nearly half of my respondents had longer walks to their back-up sources. Badowski et al (2011) found water collection times in Dar es Salaam to be less than 20-min roundtrip, but noted that households make between 2 and 5 trips each day. In Buguruni, households spend an average of thirty minutes fetching water, but half spend considerably more -over an hour (Kyessi, 2005).…”
Section: Water Collection Burdenmentioning
confidence: 99%